Una descripció lingüística desconeguda de les comarques del sud del País Valencià al segle XIX - Bernat Baltrons, Francesc (Caplletra. Revista Internacional de Filologia, 2017)
An edition consisting of a commentary on two unpublished documents that Manuel Milà i Fontanals bequeathed to their disciple Menéndez Pelayo. With the help of various sources, Milà describes some of the characteristics of the various Catalan dialects spoken in Alicante in the last third of the 19th century. He draws the southern boundary with Castilian, and takes note of some aspects of their socio-linguistic vitatily. Baltrons corrects some of the data presented by the 19th century scholar, and sets both texts in the context of the process of linguistic susbstitution in practice at that time.